Glomus tumor in a patient suffering from Von Recklinghausen disease. A case presentation. - Alfredo Oliver Martín; Wilfredo Díaz de León; Jorge Roca; Ricardo Souza Bello (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
This is a case of a pacient with Von Recklinghausen desease background, she suffers from pain since 2 years evolution in the pulpex of the second finger in the right hand. A physical and radiographic examination is done and a solitary glomal tumor is diagnosed. She goes under surgical treatment with exeresis and biopsia of the lesion. The anatomopathological examination confirmed the glomal tumor diagnosis.